The illustrated handscroll Tale of Genji - Tokio, Suzuki; Tsuneo, Fukada; Video Champ (Princeton, NJ : Films for the Humanities, 1993)
Discusses Murasaki Shikibu's novel, relating it to world literature, tracing the plot through the panels of a series of illustrated handscrolls dating to the early 12th century. These fragments of the novel are now held in the Suntory Art Museum and considered national treasures
Camera, Ohta Fumio ; overall editorial supervision, Akiyama Terukazu ; music, Sugihara Yoko ; English version, Kitamura Mitsufumi, Yano Shinya ; English script, Margaret M. Kanada
Commentary, Tokugawa Yoshinobu ; narration, Beth A. Lischeron
Keywords: Japanese literature; Japan -- Social life and customs